Socio-economic determinants of energy consumption: An empirical survey for Greece. (May 2016) - Azam, Muhammad; Khan, Abdul Qayyum; Zafeiriou, Eleni; Arabatzis, Garyfallos
Abstract: The present study identifies and evaluates the macroeconomic factors that determine energy consumption in Greece. This study is based on annual time series data covering the period ranging from 1975–2013. The Augmented Dickey Fuller (ADF) test and KPSS test are employed in order to test stationarity of the data, confirming that all the variables are I(1). Within the next step of the methodology we employed a VECM model in order to detect causality among the variables through the Granger causality test. Similarly, the impulse response analysis provides that urbanization, infrastructure, trade, income, population growth, and foreign direct investment are the main determinants of energy consumption in Greece during the period surveyed. The findings suggest that in order to fulfill the energy demand in the country, the decision-makers need to formulate energy policy in favor of enlarging the supply of energy and especially renewable energy to foster the process of economic growth and development. Especially, in the times of crisis the particular determinants are a necessity to initiate economic growth.